Analisis de los efectos de la evasion de impuestos en Colombia, Chile y Argentina - Aguilar Sarria, Karen Julieth (Universidad Antonio Nariño, 2021)
Taxes are the most important income of a country and their development depends on a large scale. In this article we will deal with the national taxes that the states of Colombia, Argentina and Chile have in common, we will go into their regulatory entities together with their working methods and we will also analyze the causes of tax evasion in these.